Regime type, inequality, and redistributive transfers in developing countries - Marina Dodlova; Anna Giolbas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The debate on whether democracy and inequality increase the level of redistribution is ongoing. We construct a model that predicts higher probability of redistribution in democracies than autocracies through social transfers. Higher inequality leads to more redistribution in democracies but not necessarily in autocracies. Using the new data on Non-Contributory Social Transfer Programmes for 1990-2015, we find democracies are more likely to have a transfer programme. This is consistent with previous conclusions that democracy enhances redistribution measured by tax revenues and government expenditures. We also present less robust evidence that countries with a transfer programme experience higher inequality.
Keywords: D72; H53; H75; 330; regime type; redistribution; inequality; social transfers; median voter theorem